GENDER PERSPEKTIF HADITS - sri mulyati (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2023)
Talking about the conception of gender in the perspective of Hadith, we first need to understand the basic references to the teachings that Muslims believe are related to the pattern of relations between men and women. The first reference is the Al-Qur'an, Muslims believe that it is the first source of Islam which is a reference for the faith of all Muslim life behaviors based on the texts of the Al-Qur'an. In a more interesting discussion of hadith, it will be the core discussion, so that when interpreted in a mawdhui (thematic) way, it is usually referred to by the term, syarh al-hadith bi al-mawdhu'iy, or in relation to understanding hadith, a thematic approach (mawdu'i) to understand the meaning and capture the meaning contained in the hadith by studying other hadiths related to the same topic of discussion and paying attention to the correlation of each so that a complete understanding is obtained. This research on women's leadership is a library research with the Thematic Hadith approach. Thematic Hadith means setting a theme to be used as material for comprehensive study. In this study, a theme was set: Gender Perspective of Hadith, hadith studies. The concept of gender has been formulated in the thematically tagged and prescribed hadiths. However, before the hadiths are recited and disyarah, the author concludes that the gender referred to in this study contains an interpretation of equality of position between women and men in carrying out all activities in accordance with the nature of each Hadith, regarding women's leadership in domestic politics. The steps as well as from the aspect of the sanad are also valid, but understanding must be through a socio-historical approach because this hadith is not always factual.